Odpowiedzi

2010-01-26T18:33:08+01:00
A) 6-4(y-3)=28
6-4y+12=28
18-4y=28
-4y=10
y=-2i2/4
b) 15x=3(1-7x)=9x
15x-3-21x=9x
-3x=3
x=-1
c)2(3-x)-4(x-5)=2x+2
6-2x-4x+20=2x+2
-8x=-24
x=3
d)0,2(0-5x)=3=2(x+1)
0-1x-3=2x+2
-3x=5
x=-1i2/3
e)(20-4x)* 0,5-7=37
10-2x-7=37
-2x=34
x=-17
2010-01-26T18:33:39+01:00
A) 6-4(y-3)=28
6-4y+12=28
-4y=10 / :(-4)
y = -2,5

b) 15x=3(1-7x)-9x
15x=3+21x-9x
3x=3 / :3
x=1

c)2(3-x)-4(x-5)=2x+2
6-2x-4x+20=2x+2
-8x=-24 / :(-8)
x = 3

d)0,2(0-5x)=3-2(x+1)
-x=3-2x+2
x=5

e)(20-4x)*0,5-7=37
10-2x-7=37
-2x = 32 / :(-2)
x = -16
2010-01-26T18:36:28+01:00
A)6-4y+12=28
-4y=28-6-12
-4y=10
y=-2,5
c)2(3-x)-4(x-5)=2x+2
6-2x-4x+20=2x+2
-8x=-24
x=3

d)0,2(0-5x)=3=2(x+1)
-x=3=2x+2
-3x=-1
x=¹₃

e)(20-4x)* 0,5-7=37
10-2x-7=37
-2x=37+7-10
-2x=34
x=-17